Pest Control Compounds Targeting Insect Chemoreceptors: Another Silent Spring? - Andersson, Martin N.; Newcomb, Richard D. (Frontiers in Ecology and Evolution, 2017)
An emerging concept in the on-going battle against insect pests is that compounds that influence the behavior of insects by modulating their ability to smell could be developed by targeting their chemoreceptors. This idea was identified by the annual horizon scan of global conservation issues as a topic of concern for their 2015 report. Unfortunately, the publication could only afford a short discussion of the pros and cons of the approach. Here we review the concept and discuss how it might be best implemented to avoid potential off-target effects and environmental harm. We describe the first of this class of compounds, VUAA1, outlining that its highly broad range of potential insect targets would lead to many of the issues associated with broad-spectrum insecticides. We also review compounds and approaches targeting the relatively less conserved carbon dioxide receptor complex and finally highly tuned receptors to conclude that focusing on species-specific pheromone receptors would result in fewer potential off-target effects.